Clinically significant anti-Wra antibody: a report of two successfully managed patients - Bujandrić, Nevenka; Kocić, Neda; Dinić, Radovan; Grujić, Jasmina (Vojnosanitetski pregled, 2025)
Introduction. Wra is an antigen of the Diego blood group system. Anti-Wra antibody can be found in the sera of healthy individuals (naturally occurring anti-Wra) or can be immunostimulated after transfusion or after exposure to foreign erythrocytes during pregnancy. Commercial antibody identification panels do not routinely contain Wra antigen-positive erythrocytes. We present two cases of patient blood management in complex situations, such as antibody appearance to low-frequency Wra antigen. Case report. In the first presented patient, who received multiple blood transfusions, anti-Wra antibody was detected while solving cross-match incompatibility.  In the second patient, anti-Wra antibody was identified during routine antierythrocyte antibody screening during pregnancy. Immunohematological testing included blood typing and antibody screening, cross-matching, antibody identification, indirect antiglobulin test (IAT), and direct antiglobulin test (DAT). Column agglutination technology with microtubes containing gel and standard tube test methodology were used in IAT and DAT. Conclusion. Due to the limitations of the screening test in detecting antibodies to clinically significant low-frequency blood group antigens, such as Wra, the recommendation when selecting erythrocytes or transfusion is to use units that are cross-match compatible by the IAT test at 37 ºC. In the case of anti-Wra antibody, as well as in cases of other antibodies to low-frequency antigens, immunohematology findings should be confirmed in a national or international reference laboratory that has the structure, organization, as well as technical and professional capacities to provide this service.
Keywords: antigens; diagnosis; erythrocyte; erythrocyte transfusion; pregnancy; transfusion reaction